1998
DOI: 10.1002/hep.510270120
|View full text |Cite
|
Sign up to set email alerts
|

Selective bowel decontamination of recipients for prevention against liver injury following orthotopic liver transplantation: Evaluation with rat models†

Abstract: Gut-derived substances can activate Kupffer cells to provoke hepatic necrosis after partial hepatectomy in rats.A similar situation may occur during orthotopic liver transplantation (OLT), as congestion in the intestinal wall, caused by portal vein occlusion, is inevitable during the operation. The contribution of such substances to liver injury following OLT was investigated in rats. Oral administration of polymyxin B sulfate for 7 days significantly altered intestinal bacterial flora in rats; Enterobacteriac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 45 publications
2
27
0
1
Order By: Relevance
“…Along this line, studies have reported an increase in TNF levels after rat liver transplantation, whereas no increase in plasma TNF was detected in recipient rats, in which intestine was resected, or in splanchnic rats (5). In addition, it has also been reported that the intestine, as a consequence of splanchnic congestion, could indirectly contribute to the increase in plasma TNF levels after liver transplantation (7,41). Thus, these authors suggest that the intestinal release of some proinflammatory mediators could stimulate TNF production in Kupffer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Along this line, studies have reported an increase in TNF levels after rat liver transplantation, whereas no increase in plasma TNF was detected in recipient rats, in which intestine was resected, or in splanchnic rats (5). In addition, it has also been reported that the intestine, as a consequence of splanchnic congestion, could indirectly contribute to the increase in plasma TNF levels after liver transplantation (7,41). Thus, these authors suggest that the intestinal release of some proinflammatory mediators could stimulate TNF production in Kupffer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogenicity of endotoxin delivered to the liver as a consequence of portal occlusion is well known (11). Consequently, two monoclonal antibodies (mAb) whose antigen binding sites are directed against a common epitope of the LPS molecule were used.…”
Section: Introductionmentioning
confidence: 99%
“…Germfree mice lack MAMPs in the portal circulation, and this absence of MAMPs appears to correlate with lower levels of hepatic leukocyte adhesion molecule expression and reduced numbers of Kupffer cells. Consistent with these studies, treatment of rats with polymyxin B prior to liver transplantation reduced intestinal levels of Enterobacteriaceae; this reduction was correlated with decreased portal circulation endotoxin levels, decreased hepatic Kupffer cell tissue factor activity, and decreased posttransplant hepatonecrosis (87). Thus, after ischemia-reperfusion, MAMPs may participate in recruitment of Kupffer cells to the liver allograft, contributing to graft injury after liver transplantation (88).…”
Section: Immunologic Consequences Of Dysbiosis Aftermentioning
confidence: 63%